Probing the strongly driven spin-boson model in a superconducting quantum circuit - L. Magazzù (Nature Portfolio, 2018)
Two-level systems interacting with a bosonic environment appear everywhere in physics. Here, the authors use a superconducting device to study this spin-boson model in the presence of coherent driving, showing that the drive enhances dissipation into the environment and can localize or delocalize the system.